Gestational high-fat diet and bisphenol A exposure heightens mammary cancer risk. Issue 7 (July 2017) - Leung, Yuet-Kin; Govindarajah, Vinothini; Cheong, Ana; Veevers, Jennifer; Song, Dan; Gear, Robin; Zhu, Xuegong; Ying, Jun; Kendler, Ady; Medvedovic, Mario; Belcher, Scott; Ho, Shuk-Mei
Abstract : In utero exposure to bisphenol A (BPA) increases mammary cancer susceptibility in offspring. High-fat diet is widely believed to be a risk factor of breast cancer. The objective of this study was to determine whether maternal exposure to BPA in addition to high-butterfat (HBF) intake during pregnancy further influences carcinogen-induced mammary cancer risk in offspring, and its dose–response curve. In this study, we found that gestational HBF intake in addition to a low-dose BPA (25 µg/kg BW/day) exposure increased mammary tumor incidence in a 50-day-of-age chemical carcinogen administration model and altered mammary gland morphology in offspring in a non-monotonic manner, while shortening tumor-free survival time compared with the HBF-alone group. In utero HBF and BPA exposure elicited differential effects at the gene level in PND21 mammary glands through DNA methylation, compared with HBF intake in the absence of BPA. Top HBF + BPA-dysregulated genes ( ALDH1B1, ASTL, CA7, CPLX4, KCNV2, MAGEE2 and TUBA3E ) are associated with poor overall survival in The Cancer Genomic Atlas (TCGA) human breast cancer cohort ( n  = 1082). Furthermore, the prognostic power of the identified genes was further enhanced in the survival analysis of Caucasian patients with estrogen receptor-positive tumors. In conclusion, concurrent HBF dietary and a low-dose BPA exposure during pregnancy increases mammary tumor incidence in offspring, accompanied by alterations in mammary gland development and gene expression, and possibly through epigenetic reprogramming.